Comparative study of the in-hospital case-fatality rate of leptospirosis between pediatric and adult patients of different age groups - Lopes, Antonio Alberto; Costa, Everaldo; Costa, Yara Aragão; Sacramento, Edilson; Oliveira Junior, Antonio Ralph Ribeiro de; Lopes, Marcelo Barreto; Lopes, Gildete Barreto (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
The main objective was to compare the in-hospital case-fatality rate of leptospirosis between pediatric (< 19 years) and adult (>;19 years) patients, taking into account gender, renal function, duration of symptoms and jaundice. Medical records of 1016 patients were reviewed. Comparative analysis was restricted to 840 patients (100 pediatric, 740 adults) with recorded information on the variables included in the analysis. Among these patients 81.7% were male and 91.5% were icteric. The case-fatality rate of leptospirosis was 14.4%. The odds of death adjusted for gender, jaundice, duration of symptoms, serum urea and serum creatinine were almost four times higher for the adult than for the pediatric group (odds ratio (OR) = 3.94; 95% confidence interval = 1.19-13.03, p = 0.029). Among adults, increased age was also significantly and independently associated with increased risk of death (p < 0.01). Older patients were also more often treated by dialysis. In conclusion, the data suggest that the in-hospital case fatality rate of leptospirosis is higher for adults than for children and adolescents, even after taking into account the effects of several potential risk factors of death. Among adults, older age was also strongly and independently associated with higher risk of death.